Resonant X-ray photoelectron spectroscopy: identification of atomic contributions to valence states. (11th May 2022) - Seymour, J. M.; Gousseva, E.; Bennett, R. A.; Large, A. I.; Held, G.; Hein, D.; Wartner, G.; Quevedo, W.; Seidel, R.; Kolbeck, C.; Clarke, C. J.; Fogarty, R. M.; et al.
Abstract : We demonstrate the validity of using valence resonant X-ray photoelectron spectroscopy to identify atomic contributions for both solutes and solvents. Abstract : Valence electronic structure is crucial for understanding and predicting reactivity. Valence non-resonant X-ray photoelectron spectroscopy (NRXPS) provides a direct method for probing the overall valence electronic structure. However, it is often difficult to separate the varying contributions to NRXPS; for example, contributions of solutes in solvents or functional groups in complex molecules. In this work we show that valence resonant X-ray photoelectron spectroscopy (RXPS) is a vital tool for obtaining atomic contributions to valence states. We combine RXPS with NRXPS and density functional theory calculations to demonstrate the validity of using RXPS to identify atomic contributions for a range of solutes (both neutral and ionic) and solvents (both molecular solvents and ionic liquids). Furthermore, the one-electron picture of RXPS holds for all of the closed shell molecules/ions studied, although the situation for an open-shell metal complex is more complicated. The factors needed to obtain a strong RXPS signal are investigated in order to predict the types of systems RXPS will work best for; a balance of element electronegativity and bonding type is found to be important. Additionally, the dependence of RXPS spectra on both varying solvation environment and varying local-covalent bonding is probed. We find that RXPS is a promising fingerprint method for identifying species in solution, due to the spectral shape having a strong dependence on local-covalency but a weak dependence on the solvation environment.